2024
DOI: 10.1038/s41467-024-49087-2
|View full text |Cite
|
Sign up to set email alerts
|

FBXO7 ubiquitinates PRMT1 to suppress serine synthesis and tumor growth in hepatocellular carcinoma

Li Luo,
Xingyun Wu,
Jiawu Fan
et al.

Abstract: Cancer cells are often addicted to serine synthesis to support growth. How serine synthesis is regulated in cancer is not well understood. We recently demonstrated protein arginine methyltransferase 1 (PRMT1) is upregulated in hepatocellular carcinoma (HCC) to methylate and activate phosphoglycerate dehydrogenase (PHGDH), thereby promoting serine synthesis. However, the mechanisms underlying PRMT1 upregulation and regulation of PRMT1-PHGDH axis remain unclear. Here, we show the E3 ubiquitin ligase F-box-only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(57 reference statements)
1
2
0
Order By: Relevance
“…2D). Similar to the literature (Luo et al, 2024), we observed that PRMT1 has a relatively long half-life of approximately 15 hours when unperturbed, which is significantly shortened by p300 overexpression and extended by p300 inhibition (Fig. 2D).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…2D). Similar to the literature (Luo et al, 2024), we observed that PRMT1 has a relatively long half-life of approximately 15 hours when unperturbed, which is significantly shortened by p300 overexpression and extended by p300 inhibition (Fig. 2D).…”
Section: Resultssupporting
confidence: 90%
“…Given the importance of PRMT1 homeostasis to cellular arginine methylation, there are multiple mechanisms by which PRMT1 can be degraded. For example, it has also been reported to be modulated by other E3 ligases, including TRIM48 (Hirata et al, 2017) and FBXO7 (Luo et al ., 2024). Excitingly, both the TRIM48-PRMT1 and FBXO7-PRMT1 interactions are preliminarily evidenced to be viable therapeutic targets for inhibiting oncogenic metabolism exhibited by hepatocellular carcinoma (Li et al ., 2023; Luo et al ., 2024).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation